2009
DOI: 10.1111/j.1469-8137.2009.02770.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific, age‐dependent sensitivity of tree‐ring growth to climate in the dioecious tree Juniperus thurifera

Abstract: Summary• Tree features may modulate the sensitivity of radial growth to climate, leading to a nonuniform response. Age-related increases in climatic sensitivity have been observed repeatedly. Sex-related climatic sensitivity is also possible because of the long-term differential reproductive cost between the sexes. This study analysed the simultaneous effects of age and sex on the sensitivity of tree-ring growth to climate.• Ring widths were measured from 50 female and 50 male Juniperus thurifera trees, 50-350… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
121
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(135 citation statements)
references
References 58 publications
10
121
3
1
Order By: Relevance
“…In the last decades, increasing evidence suggests that tree response to the climate is modulated by several endogenous factors, such as the genotype [11], age [12], size [13], and sex [14], in addition to exogenous factors of abiotic [15] and biotic nature [16,17]. Thus, population-based approaches might miss part of the wide range of individual responses that exist within a stand [18], obliterating different sources of variability that could contribute to more adequate management policies, or simply provide a better prediction of the individual growth responses to climate.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, increasing evidence suggests that tree response to the climate is modulated by several endogenous factors, such as the genotype [11], age [12], size [13], and sex [14], in addition to exogenous factors of abiotic [15] and biotic nature [16,17]. Thus, population-based approaches might miss part of the wide range of individual responses that exist within a stand [18], obliterating different sources of variability that could contribute to more adequate management policies, or simply provide a better prediction of the individual growth responses to climate.…”
Section: Introductionmentioning
confidence: 99%
“…Previous dendroclimatic studies in central Spain and the French Pyrenees have shown that secondary growth of /. thurifera is mainly controlled by winter precipitation, spring temperature, and summer water stress (Bertaudiére et al 1999;Rozas et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Tree growth at an old age can be more limited by climate, as growth trend can be relatively more stable in old trees compared to younger trees [43][44][45][46]. Hence, our projections here might be biased towards old trees.…”
Section: Discussionmentioning
confidence: 89%